Distribution of Income in India : The Story of Divergence Since 1991 - Jasmin (Arthshastra Indian Journal of Economics & Research, 2020)
The issue of income distribution holds great significance; it is one of the oldest questions in economics, touched upon by prominent thinkers. Growth of income and its distribution have long been perceived as intertwined issues. Growth of profits at the expense of wages can have far-reaching effects for the economy. This study focused on a particular facet of inequality. The marginalization of small peasants, agricultural labour, and the presence of a huge pool of non-farm wage workers has been fuelling incomes of the rich not just in Indian agriculture, but manufacturing and services as well. The informal and unskilled workers in the industry have taken the hit to allow room for further growth in the incomes of owners as well as managerial and skilled classes. With this backdrop, the mainstay of this research work was to examine the trends in profit and wage share for India and the skewed distribution of factor shares, particularly in the post reform period, spanning manufacturing and services sectors. The paper discussed the connect between abysmal conditions in the Indian agriculture sector and rising profits as well as growth in wage inequality in manufacturing and service sectors. Data from multiple sources was utilized to explore the inequality in the distribution of factor incomes in India. The paper highlighted that both income and wealth inequality in India have grown in the post reform period. The study found empirical evidence in support of growing capital incomes in all the three sectors and rising wage differentials in manufacturing and service sectors.